The Role of the Police in Combating the Crime of Cockfighting Gambling - Eko Adi Setiawan; Herman Bakir; Boy Nurdin (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Gambling practices that have various kinds and techniques are very easy to do, making this gambling very rapidly growing in countries around the world and one of them is Indonesia. Although gambling is prohibited and contrary to applicable law in Indonesia. Gambling is very detrimental to society and the nation's morals. Order, security, and peace in society are disrupted as a result of gambling. In addition, the impact of this gambling is that it can lead to crimes such as theft, molestation, murder, and even interference in a relationship in the household which results in domestic violence. The government's steps in taking action against gambling crimes are by issuing regulations such as Article 303 of the Criminal Code and in Law no. 7 of 1974 concerning the regulation of gambling. In addition to the issuance of regulations by the government, the police also take part in dealing with gambling crimes through preventive and repressive efforts. Preventive action is a way that the police do before a crime occurs. In this case, the efforts made by the police in uncovering the crime of gambling in the community include investigations, finding sources of information, spying, snooping, making arrests, and confiscating evidence and socialization. Repressive efforts are also one of the methods used by the police in dealing with cockfighting gambling during this activity. The police immediately raided the cockfighting gambling place and arrested everyone who was directly involved in the cockfighting gambling activity.